Tax Compliance among Small and Medium Manufacturing Enterprises in Kenya: Does Tax Morale Matter? - Morris Karithi Njilu (Rowter Journal, 2023)
The study sought to assess the impact of tax morale on tax compliance among SMEs in Nairobi County, Kenya. Most governments especially the developing ones and particularly Kenya rely on taxes as their main source of revenue to run their development agenda. Kenyan SMEs have been in the forefront as the major contributors to Kenya’s economic growth and development. However, in the recent past there has been increased tax evasion from the sector. This signifies a continued drop in the government revenue and failure by the tax collection authority; KRA to meet the set targets in annual revenue collection. Tax morale has been found to be a key aspect contributing significantly to tax compliance. Locally, it remains unclear on how tax morale influences tax compliance with very few studies focusing on the area locally and of those few focusing on other industries. Descriptive research design was used in the study and the target population was the 1539 registered SMEs in Nairobi CBD. A sampling formula was used to identify a sample size of 318 respondents who were picked through stratified random sampling with the categories of SMEs as the strata. Structured questionnaire was used to collect data for the study which was analysed through descriptive and inferential statistics. The study established that tax morale significantly influenced the tax compliance by the SMEs. It was established that the morale of tax payers was affect by inappropriate use of the collected taxes, lack of the required information, and minimal support from the government, thus affecting the compliance levels. The study concluded that tax evasion has escalated mainly as a result on reduced morale among tax payers due to inappropriate se of the collected taxes and poor accountability among government officials. Enhancing accountability and ensuring responsible use would be essential to enhance tax compliance.